Building a Product Category System for a Shopping App with Inheritance in Java - Saluky Saluky; Revi Injani; Citta Amelia (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2024)
This article discusses the development of a product category system for an online shopping application using the concept of inheritance in Java programming. In a shopping application, efficient product category management is essential to make it easier for users to search for items according to their type and preferences. This system is designed using an inheritance structure to define various product categories hierarchically. The parent category will provide basic attributes and methods, while the child category will inherit and develop these functionalities according to the specific needs of the product. The use of inheritance allows for more modular and manageable coding, and increases the ability to expand the application in the future. With this system, the shopping application not only simplifies the product search process but also allows for more structured and flexible product grouping. The implementation in Java is done using base classes and child classes, as well as a polymorphism mechanism to optimize interactions between product category objects. The results of this study indicate that an inheritance-based approach in Java can improve the efficiency and readability of code in developing shopping applications with dynamic and easily developed product categories.